Answer: you subtract the number of protons from the mass number, on the periodic table your atomic number is your protons and your atomic mass is the mass number
Explanation:
![\textbf{A}×\textbf{B}= 68\hat{\textbf{i}} + 52\hat{\textbf{j}} - 8\hat{\textbf{k}}](https://tex.z-dn.net/?f=%5Ctextbf%7BA%7D%C3%97%5Ctextbf%7BB%7D%3D%2068%5Chat%7B%5Ctextbf%7Bi%7D%7D%20%2B%2052%5Chat%7B%5Ctextbf%7Bj%7D%7D%20-%208%5Chat%7B%5Ctextbf%7Bk%7D%7D)
Explanation:
Given:
![\textbf{A} = 5\hat{\textbf{i}} - 7\hat{\textbf{j}} - 3\hat{\textbf{k}}](https://tex.z-dn.net/?f=%5Ctextbf%7BA%7D%20%3D%205%5Chat%7B%5Ctextbf%7Bi%7D%7D%20-%207%5Chat%7B%5Ctextbf%7Bj%7D%7D%20-%203%5Chat%7B%5Ctextbf%7Bk%7D%7D)
![\textbf{B} = -4\hat{\textbf{i}} + 4\hat{\textbf{j}} - 8\hat{\textbf{k}}](https://tex.z-dn.net/?f=%5Ctextbf%7BB%7D%20%3D%20-4%5Chat%7B%5Ctextbf%7Bi%7D%7D%20%2B%204%5Chat%7B%5Ctextbf%7Bj%7D%7D%20-%208%5Chat%7B%5Ctextbf%7Bk%7D%7D)
The cross product
is given by
![\textbf{A}×\textbf{B} = \left|\begin{array}{ccc}\hat{\textbf{i}} & \hat{\textbf{j}} & \hat{\textbf{k}} \\\:\:5 & -7 & -3 \\ -4 & \:\:4 & -8 \\ \end{array}\right|](https://tex.z-dn.net/?f=%5Ctextbf%7BA%7D%C3%97%5Ctextbf%7BB%7D%20%3D%20%5Cleft%7C%5Cbegin%7Barray%7D%7Bccc%7D%5Chat%7B%5Ctextbf%7Bi%7D%7D%20%26%20%5Chat%7B%5Ctextbf%7Bj%7D%7D%20%26%20%5Chat%7B%5Ctextbf%7Bk%7D%7D%20%5C%5C%5C%3A%5C%3A5%20%26%20-7%20%26%20-3%20%5C%5C%20-4%20%26%20%5C%3A%5C%3A4%20%26%20-8%20%5C%5C%20%5Cend%7Barray%7D%5Cright%7C)
![= \left|\begin{array}{cc}-7 & -3\\\:4 & -8\\ \end{array}\right|\:\hat{\textbf{i}}\:+\:\left|\begin{array}{cc}-3 & \:\:5\\-8 & -4\\ \end{array}\right|\:\hat{\textbf{j}}\:+\: \left|\begin{array}{cc}\:\:5 & -7\\-4 & \:\:4\\ \end{array}\right|\:\hat{\textbf{k}}](https://tex.z-dn.net/?f=%3D%20%20%5Cleft%7C%5Cbegin%7Barray%7D%7Bcc%7D-7%20%26%20-3%5C%5C%5C%3A4%20%26%20-8%5C%5C%20%5Cend%7Barray%7D%5Cright%7C%5C%3A%5Chat%7B%5Ctextbf%7Bi%7D%7D%5C%3A%2B%5C%3A%5Cleft%7C%5Cbegin%7Barray%7D%7Bcc%7D-3%20%26%20%5C%3A%5C%3A5%5C%5C-8%20%26%20-4%5C%5C%20%5Cend%7Barray%7D%5Cright%7C%5C%3A%5Chat%7B%5Ctextbf%7Bj%7D%7D%5C%3A%2B%5C%3A%20%5Cleft%7C%5Cbegin%7Barray%7D%7Bcc%7D%5C%3A%5C%3A5%20%26%20-7%5C%5C-4%20%26%20%5C%3A%5C%3A4%5C%5C%20%5Cend%7Barray%7D%5Cright%7C%5C%3A%5Chat%7B%5Ctextbf%7Bk%7D%7D)
![= 68\hat{\textbf{i}} + 52\hat{\textbf{j}} - 8\hat{\textbf{k}}](https://tex.z-dn.net/?f=%3D%2068%5Chat%7B%5Ctextbf%7Bi%7D%7D%20%2B%2052%5Chat%7B%5Ctextbf%7Bj%7D%7D%20-%208%5Chat%7B%5Ctextbf%7Bk%7D%7D)
Answer:
Explanation:
Given height of lamp from the ceiling = 2.6m
mass of the lamp = 3.8kg
acceleration due to gravity = 9.81m/s²
As the body falls to the ground, it falls under the influence of gravity.
Gravitational potential energy = mass*acc due to gravity * height
Gravitational potential energy = 3.8*2.6*9.81
Gravitational potential energy = 96.923 Joules
b) Kinetic energy = 1/2 mv²
m = mass of the body (in kg)
v = velocity of the body (in m/s²)
To get the velocity v, we will use the equation of motion ![v^{2} = u^{2}+2gh](https://tex.z-dn.net/?f=v%5E%7B2%7D%20%3D%20u%5E%7B2%7D%2B2gh)
![v^{2} = 0^{2}+2(9.81)(2.6) \\v^{2} = 51.012\\v =\sqrt{51.012}\\ v = 7.14m/s](https://tex.z-dn.net/?f=v%5E%7B2%7D%20%3D%200%5E%7B2%7D%2B2%289.81%29%282.6%29%20%5C%5Cv%5E%7B2%7D%20%3D%2051.012%5C%5Cv%20%3D%5Csqrt%7B51.012%7D%5C%5C%20v%20%3D%207.14m%2Fs)
Since mass = 3.8kg
![K.E = 1/2 * 3.8 *7.14^{2}\\ K.E = 96.86Joules](https://tex.z-dn.net/?f=K.E%20%3D%20%201%2F2%20%2A%203.8%20%2A7.14%5E%7B2%7D%5C%5C%20K.E%20%3D%2096.86Joules)
c) To know how fast the lamp is moving when it hits the ground, we will use the formula. When the body hits the ground, the height covered will be 0m. this means that the body is not moving once it hits the ground. It stays in one position. The energy possessed by the body at this point is potential energy. The correct answer is therefore 0 m/s
Answer:
a. 4
Explanation:
Hi there!
The equation of kinetic energy (KE) is the following:
KE = 1/2 · m · v²
Where:
m = mass of the car.
v = speed of the car.
Let´s see how would be the equation if the velocity is doubled (2 · v)
KE2 = 1/2 · m · (2 · v)²
Distributing the exponent:
KE2 = 1/2 · m · 2² · v²
KE2 = 1/2 · m · 4 · v²
KE2 = 4 (1/2 · m · v²)
KE2 = 4KE
Doubling the velocity increased the kinetic energy by 4.